Modeling of chloride penetration in concrete structures under freeze-thaw cycles. Issue 1 (26th July 2019) - Hamidane, H'mida; Ababneh, Ayman; Messabhia, Ali; Xi, Yunping
Abstract : Purpose: The purpose of this paper is to develop a method for predicting the chloride ingress into concrete structures, with an emphasis on the low temperature range where freeze-thaw cycles may cause damage. Design/methodology/approach: The different phenomena that contribute to the rate and amount of transported chlorides into concrete, i.e., heat transfer, moisture transport and chloride diffusion are modeled using a two-dimensional nonlinear time dependent finite element method. In modeling the chloride transport, a modified version of Fick's second law is used, in which processes of diffusion and convection due to water movement are taken into account. Besides, the effect of freeze-thaw cycles is directly incorporated in the governing equation and linked to temperature variation using a coupling term that is determined in this study. The proposed finite element model and its associated program are capable of handling pertinent material nonlinearities and variable boundary conditions that simulate real exposure situations. Findings: The numerical performance of the model was examined through few examples to investigate its ability to simulate chloride penetration under freeze-thaw cycles and its sensitivity to factors controlling freeze-thaw damage. It was also proved that yearly temperature variation models to be used in service life assessment should take into account its cyclic nature to obtain realistic predictions. Originality/value: The model proved promising and suitable for chloride penetration in cold climates.